Солнечноэнергетические ресурсы Одесской области и методика их оценки = Solar energy resources of Odessa region and methods of its evalution - Yavorckaya, V. V.; Svetlichnaya, D. A. (Journal of Education, Health and Sport, 2016)
Yavorckaya V. V., Svetlichnaya D. A. Солнечноэнергетические ресурсы Одесской области и методика их оценки = Solar energy resources of Odessa region and methods of its evalution. Journal of Education, Health and Sport. 2016;6(10):68-78. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.160192 http://ojs.ukw.edu.pl/index.php/johs/article/view/3927 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 03.10.2016. Revised 11.10.2016. Accepted: 12.10.2016. УДК 911.3 СОЛНЕЧНОЭНЕРГЕТИЧЕСКИЕ РЕСУРСЫ ОДЕССКОЙ ОБЛАСТИ И МЕТОДИКА ИХ ОЦЕНКИ В. В. Яворская, Д. А. Светличная Одесский национальный университет им. И. И. Мечникова, Кафедра экономической и социальной географи и туризма Резюме Цели. Важным стратегическим направлением развития энергетики в Украине является использование нетрадиционных возобновляемых источников энергии, что является одним из важных критериев устойчивого развития общества. Необходимость использования нетрадиционных возобновляемых источников энергии обуславливается исчерпанием запасов органических видов топлива, резко возросшей цены на них, несовершенная и низкая эффективность технологий их использования, вредное воздействие на окружающую среду, последствия которого все больше и больше беспокоят мировое сообщество. Одним из перспективных видов возобновляемых источников энергии является энергия солнца. Кроме того, вся территория Украины пригодна для развития систем теплоснабжения с использованием солнечной энергии. Основываясь на этих постулатах и выполнена представленная в статье пространственно-распределенная оценка солнечноэнергетических ресурсов Одесской области. Материалы и методы. В качестве материалов для написания статьи использованы публикации отчественных и зарубежных ученых в области использования нетрадиционных возобновляемых источников энергии, включая статьи в отечественных и зарубежных периодических научных изданиях, монографические и учебно-методические издания, номативно-правовые акты. В ходе анализа материалов применены общенаучные методы исследований – сравнение, описание, анализ, синтез, обобщение, системный подход. Основные результаты и выводы. В основу оценки потенциальных солнечноэнергетических ресурсов положено использование следующих категорий солнечноэнергетических ресурсов: естественный солнечноэнергетический потенциал (ЕСЭП) и технические солнечноэнергетические ресурсы (ТСЭР). Было выполнено обоснование величин, входящих в формулы оценки потенциальных солнечноэнергетических ресурсов. На основании результатов оценки потенциальных солнечноэнергетических ресурсов с помощью геоинформационных систем и технологий были построены карты: удельных (отнесенных к 1 м2) ТСЭР для территории Одесской области, которая является базовой для вычисления средствами ГИС суммарных ТСЭР для любой территории, а также карта средних для административных районов области удельных технических солнечноэнергетических ресурсов, построенная программными средствами ГИС-пакета ArcGIS Advanced. Анализ построенных карт показывает, что наибольшими удельными ТСЭР облают южные административные районы области – Килийский, Измаильский, Татарбунарский, Ренийский, города Измаил, Белгород-Днестровский, Черноморск - 145-147 кВт час/(м2 год), наименьшими – северные административные районы: Кодымский, Подольский, Балтский, Савранский и г. Подольск (130-134 кВт час/(м2 год). Ключевые слова: потенциальные солнечноэнергетические ресурсы, Одесская область, пространственно-распределенная оценка, ГИС-технологии. SOLAR ENERGY RESOURCES OF ODESSA REGION AND METHODS OF ITS EVALUATION V. V. Yavorckaya, D. A. Svetlichnaya Odessa I. I. Mechnikov National University, Department of Economic and Social Geography and Tourism Abstract Purpose. Important strategic direction of development of energy sector ofUkraine is the use of renewable energy resources, which is one of the important criteria of sustainable development of the society. The necessity of using alternative renewable energy resources is caused by the depletion of fossil fuels, sharply increased prices for them, imperfect technologies and low efficiency of their usage, harmful effects on the environment. One of the most promising types of renewable energy is the solar energy. Besides, the entireterritory ofUkraine is suitable for the development of district heating systems using solar energy. Based on these postulates was executed spatially-distributed evaluation of solar energy resources ofOdessa region. Data & Methods. Publication of home and foreign scientists in the field of using alternative renewable resources of energy, including articles in national and foreign scientific journals, monographs and academic publications, regulatory legal acts are used for writing this article. For the analysis of the materials general scientific research methods - comparison, description, analysis, synthesis, generalization, induction and deduction, the system approach, are used Results. The basis of evaluation of potential solar energy resources constitutes the following categories: natural solar energy potential (NSEP) and technical solar energy resources (TSER). Justification of the quantities involved in the evaluation of solar energy potential resources was carried out. Based on the results of the evaluation of solar energy potential resources using geographic information systems and technologies following maps were built: specific TSER (referred to 1 m2) for the Odessa region, which can be the base for the calculation by GIS of TSER for any territory, and the map of average specific TSER for administrative districts, which was built by ArcGIS Advanced GIS package. Analysis of maps shows that the southern administrative districts of the region - Kiliysky, Izmailskiy, Tatarbunarskiy, Reniiyskiy, cities: Izmail, Belgorod-Dnestrovskyi, Chernomorsk have the largest specific TSER - 145-147 kWh/(m2 year), the smallest - the northern administrative districts: Kodymskiy , Podolskiy, Baltskiy, Savranskiy and Podolsk city (130-134 kWh / (m2 year). Keywords: potential solar energy resources, Odessa region, spatial-distributed evaluation, GIS technology.